Health-related quality of life in maxillectomy patients undergoing dentoalveolar rehabilitation. (March 2022) - Petrides, George A.; Dunn, Masako; Charters, Emma; Venchiarutti, Rebecca; Cheng, Kai; Froggatt, Catriona; Mukherjee, Payal; Wallace, Christine; Howes, Dale; Leinkram, David; Singh, Jasvir; Nguyen, Kevin; et al.
Highlights: This is one of the first studies to use the FACE-Q Head and Neck to examine the effects of dentoalveolar rehabilitation in maxillary reconstruction on health-related quality of life (HRQOL). This is one of the first studies to demonstrate improved HRQOL and speech and swallowing function following virtual surgical planning (VSP) in maxillary reconstruction. Dentoalveolar rehabilitation is an important goal in maxillary reconstruction. Abstract: Objectives: Surgical resection of the maxilla impairs aesthetics, speech, swallowing, and mastication. Maxillary reconstruction is increasingly performed with virtual surgical planning (VSP) to enhance functional dental rehabilitation with a conventional denture or osseointegrated implants. The aim of this study was to determine whether dental status and VSP is associated with health-related quality of life (HRQOL) and function in patients who have undergone maxillectomy. Materials and methods: A cross-sectional study was conducted among patients who underwent free flap reconstruction or obturation of the maxilla between July 2009 and December 2020. The FACE-Q Head and Neck Cancer (FACE-Q) module, M.D. Anderson Dysphagia Inventory (MDADI), and Speech Handicap Index (SHI) were used to evaluate HRQOL. Results: Forty-three patients (response rate 59%) completed questionnaires and 48% underwent dental rehabilitation. In Okay Class II and III defects, adjusting for the effect of radiotherapy and time from surgery, there was a positive association between denture status and FACE-Q smiling ( p  = 0.020), eating ( p  = 0.012), smiling ( p =  0.015), and MDADI global ( p  = 0.015), emotional ( p  = 0.027), functional ( p =  0.028), and composite ( p  = 0.029) scores. VSP was associated with FACE-Q swallowing ( p  = 0.005), drooling ( p  = 0.030), eating ( p  = 0.008), smiling ( p  = 0.021), MDADI global ( p  = 0.017), emotional ( p  = 0.041), functional ( p  = 0.040), composite ( p  = 0.038), and SHI total scores ( p  = 0.042). Conclusions: Dentoalveolar rehabilitation and VSP were associated with higher HRQOL scores relating to eating and drinking, smiling, and speaking.